Inside Back Cover: Target‐Directed Azide‐Alkyne Cycloaddition for Assembling HIV‐1 TAR RNA Binding Ligands (Angew. Chem. Int. Ed. 30/2020). Issue 30 (4th June 2020) - Paul, Rakesh; Dutta, Debasish; Paul, Raj; Dash, Jyotirmayee
Abstract : A potential strategy for the rapid discovery of antiviral therapeutic agents is delineated by J. Dash and co‐workers in their Communication on page 12407 . HIV‐1 TAR RNA promotes azide–alkyne cycloadditions to generate a new class of triazole‐linked thiazole peptidomimetics as the RNA's own binders.